A comparative study of nitrilases identified by genome mining - Kaplan, Ondřej; Veselá, Alicja B; Petříčková, Alena; Pasquarelli, Fabrizia; Pičmanová, Martina; Rinágelová, Anna; Bhalla, Tek Chand; Pátek, Miroslav; Martínková, Ludmila (Molecular biotechnology, 2013)
Escherichia coli strains expressing different nitrilases transformed nitriles or KCN. Six nitrilases (from Aspergillus niger (2), A. oryzae, Neurospora crassa, Arthroderma benhamiae, and Nectria haematococca) were arylacetonitrilases, two enzymes (from A. niger and Penicillium chrysogenum) were cyanide hydratases and the others (from P. chrysogenum, P. marneffei, Gibberella moniliformis, Meyerozyma guilliermondi, Rhodococcus rhodochrous, and R. ruber) preferred (hetero)aromatic nitriles as substrates. Promising nitrilases for the transformation of industrially important substrates were found: the nitrilase from R. ruber for 3-cyanopyridine, 4-cyanopyridine and bromoxynil, the nitrilases from N. crassa and A. niger for (R,S)-mandelonitrile, and the cyanide hydratase from A. niger for KCN and 2-cyanopyridine.
Keywords: sekvenční seřazení; dehydratasy; aminohydrolasy; sekvenční homologie aminokyselin; Fungi; Substrate Specificity; fungální proteiny; Sequence Homology, Amino Acid; Sequence Analysis, DNA; houby; genomika; Hydro-Lyases; Escherichia coli; Aminohydrolases; Recombinant Proteins; sekvenční analýza DNA; rekombinantní proteiny; Genome, Fungal; substrátová specifita; Sequence Alignment; genom fungální; Genomics; Fungal Proteins